Damage mechanisms during very high cycle fatigue of a coated and grit-blasted Ni-based single-crystal superalloy. (January 2021) - Cervellon, Alice; Bortoluci Ormastroni, Luciana Maria; Hervier, Zéline; Pollock, Tresa M.; Pedraza, Fernando; Cormier, Jonathan
Highlights: Degradation mechanisms during VHCF of coated and grit-blasted CMSX-4 elucidated. VHCF life reduced by a thick RX layer without contribution of environment. Roughness degrades the oxidation resistance and the VHCF life if combined with RX. Oxidation damage in the interdiffusion zone governs VHCF life of coated specimens. Abstract: The very high cycle fatigue properties of the Ni-based single-crystal superalloy CMSX-4 coated with an MCrAlY type coating and grit-blasted were studied at 1000 °C, 20 kHz and R = -1. A recrystallized layer thicker than the size of the larger casting pores (>50 μm) drastically reduces the fatigue life without environmental influence. The recrystallized layer and roughness introduced by grit-blasting degrades the environmental resistance of the alloy and the resultant fatigue life. The fatigue life of the coated specimens is also greatly reduced from damage accumulation in the interdiffusion zone by grain boundary cracking, oxidation and internal nitridation.